2014
DOI: 10.1007/s12032-014-0086-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of GSTP1 and ERCC1 correlated with response to platinum-based chemotherapy in non-small cell lung cancer

Abstract: The study aims to investigate whether the glutathione S transferase P1 (GSTP1) and excision repair cross-complementing group 1 (ERCC1) polymorphism influence the response to treatment with platinum-based chemotherapy in Chinese patients with non-small cell lung cancer. Ninety-one patients with metastatic non-small lung cancer were evaluated. Blood samples were obtained from each patient before chemotherapy. They are all administered modified TP, GP, NP regimens. Curative effects in patients were evaluated afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 46 publications
2
30
2
Order By: Relevance
“…The predictive value of ERCC1 expression in platinum-based chemotherapy responses has been reported in various cancers such as non-small cell cancer, ovarian cancer, and cervical cancer, as well as BC (Dabholkar et al, 1994;Kong et al, 2006;Bellmunt et al, 2007;Chen et al, 2010;Hoffmann et al, 2010;Okuda et al, 2011;Park et al, 2011;Cheng et al, 2012;Lv et al, 2014). A systemic review published in 2012 further confirmed the predictive value of ERCC codon C118T polymorphism in advanced colorectal patients treated with platinum-based chemotherapy in the Asian population.…”
Section: Discussionmentioning
confidence: 79%
“…The predictive value of ERCC1 expression in platinum-based chemotherapy responses has been reported in various cancers such as non-small cell cancer, ovarian cancer, and cervical cancer, as well as BC (Dabholkar et al, 1994;Kong et al, 2006;Bellmunt et al, 2007;Chen et al, 2010;Hoffmann et al, 2010;Okuda et al, 2011;Park et al, 2011;Cheng et al, 2012;Lv et al, 2014). A systemic review published in 2012 further confirmed the predictive value of ERCC codon C118T polymorphism in advanced colorectal patients treated with platinum-based chemotherapy in the Asian population.…”
Section: Discussionmentioning
confidence: 79%
“…Currently, some studies have investigated the association between genetic polymorphisms in the GSTP1 IIe105Val region and the prognosis of advanced NSCLC, but the results are inconclusive (Ada et al, 2010;Zhou et al, 2011;Ke et al, 2012;Lv et al, 2014;Yang and Zhao, 2014;Deng et al, 2015;Han et al, 2015;Liu et al, 2015). Individuals with GSTP1 gene polymorphisms display a reduced ability to detoxify drug metabolites, thus promoting the overall survival of NSCLC (Lu et al, 2006;Ke et al, 2012;Lv et al, 2014;Deng et al, 2015;Han et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with GSTP1 gene polymorphisms display a reduced ability to detoxify drug metabolites, thus promoting the overall survival of NSCLC (Lu et al, 2006;Ke et al, 2012;Lv et al, 2014;Deng et al, 2015;Han et al, 2015). Four studies reported that the Val allele of GSTP1 IIe105Val obtained a better response to chemotherapy and a better survival time when compared to IIe allele in Asian population (Ada et al, 2010;Zhou et al, 2011;Ke et al, 2012;Lv et al, 2014;Han et al, 2015). Two studies suggested that the Val allele of GSTP1 IIe105Val was more highly correlated with a poor response to chemotherapy than those carrying the IIe genotype (Deng et al, 2015;Liu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the relationship between GSTP1 polymorphisms and prognosis of advanced NSCLC, but the results are inconclusive (Booton et al, 2006;Lu et al, 2006;Vlachogeorgos et al, 2008;Kalikaki et al, 2009;Sun et al, 2010;Lv et al, 2014;Han et al, 2015). Sun et al (2010), Han et al (2015) and Lv et al, (2014) conducted studies in Chinese populations and reported that GSTP1 genetic variations might be the predictive markers for the treatment outcome of advanced NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al (2010), Han et al (2015) and Lv et al, (2014) conducted studies in Chinese populations and reported that GSTP1 genetic variations might be the predictive markers for the treatment outcome of advanced NSCLC. Booton et al (2006), Vlachogeorgos et al (2008) and Lu et al (2006) carried out studies in Caucasians and they reported that GSTP1 polymorphisms may predict response to treatment and survival in patients with advanced NSCLC.…”
Section: Discussionmentioning
confidence: 99%